Designing and Evaluating Calibration-Driven Recommender Systems for Fairness and Explainability - Atauchi, Paul; Zanon, Andre; Rocha, Leonardo; Manzato, Marcelo (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Recommender systems are increasingly required to satisfy fairness and transparency constraints. However, the interaction between calibration-based fairness interventions and recommendation explainability remains insufficiently understood. This paper proposes a calibration-driven framework that extends single-category calibration to a multi-category setting, enabling a richer representation of user preferences across item dimensions. The approach integrates fairness-aware calibration with post-hoc knowledge-graph-based explanations into a unified pipeline. We evaluate both recommendation performance and explanation quality, considering alignment with user profiles, accuracy, miscalibration, and popularity bias, as well as explanation metrics such as recency, popularity, and diversity. Results show improved alignment, reduced miscalibration and popularity bias, and preserved accuracy, while explanation quality remains stable. These findings indicate that calibration-based fairness can be achieved without compromising explainability.